(3QSGdI aj GdgjFIs - (3GdeanqVd Hf YeQ Hf GdeaVd GdCHgQj GdSeQbfOj, CKjQ GdOjf,J (B663 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdbhje GdPi JhMO HGdYRI hGdHbGA GdYXje hHYO adeG cGfJ eYQaI GdCYeGd GdfLhejI hGdMSGHGJ GdadcjI eMJGLI Edi WQa ef Yde GdgjFI hGdMSGH s
(3BNQgG (B:s
(3hgj ai GdehVY GdPi jfWHb ajg bWH GdYGde Ydi SeJ GdQCS hdjcf gPG BNQ GdQSGdI hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3fbdJ Yf fSNI cGf ajgG NW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI eTgO cdjI GdEdgjGJ (B(1/ 51) s
Keywords: (3Gdadcs